NEW STRATEGY JAPANESE MILITARY IN THE ASIA PACIFIC REGION AND THE IMPACT ON INTERNATIONAL SECURITY STABILITY - Watanabe Yazuru (Jurnal Pembaharuan Hukum, 2022)
The purpose of this study was to determine the new Japanese military strategy in the Asia Pacific region and its impact on international security stability. The South China Sea conflict is one of the major conflicts for the Southeast Asia region and also the Asia Pacific region. Japan has a role in supporting countries involved in the conflict such as Vietnam. Japan promised Vietnam six patrol boats during Prime Minister Abe's visit to Southeast Asia.The approach used in this research is a qualitative approach and the type of research carried out is descriptive by explaining certain phenomena systematically, actually and accurately regarding facts, characteristics, and relationships. The patrol boat is aimed at enhancing Vietnam's capability in maritime law enforcement related to the South China Sea conflict. Japan, which is Vietnam's biggest foreign investor after South Korea, has no territorial claims in the South China Sea conflict. The South China Sea region has a big role in geopolitics because it is a meeting point between China and countries within the Association of Southeast Asian Nations (ASEAN) in terms of territory, security, natural resources and energy security. Disputes in the region include territorial sovereignty and maritime sovereignty. The South China Sea area consists of, among others, several small islands that are widely distributed, but there are two groups of islands that are much contested, namely the Spratly Islands and the Paracels. In addition, the South China Sea area is an important shipping lane and is often referred to as the maritime superhighway because it is one of the busiest international shipping lanes in the world.